ESTRATÉGIAS DE CONTROLE PARA USINA DE PELOTIZAÇÃO DA VALE - Paulo Rogério de Almeida Ribeiro; Tarcísio Souza Costa; Victor Hugo Barros; Areolino de Almeida Neto; Alexandre César Muniz de Oliveira (Universidade Federal do Maranhão, 2010)
Este trabalho destina-se a apresentar estratégias de controle para melhorias no desempenho do sistema de controle da usina de pelotização da Vale em São Luís do Maranhão, Brasil. A usina já detém um sistema de controle convencional, Proporcional Integral Derivativo (PID). No intuito de melhorar o desempenho faz-se uso da estratégia Feedback-Error-Learning (FEL), assim como da estratégia Multi-Network-Feedback-Error-Learning (MNFEL). No intuito de comparar estratégias não convencionais faz-se uso também de um controlador PI-Fuzzy. Estas estratégias são comparadass e seus resultados discutidos. Palavras-chave: Controle adaptativo. Redes neurais. Lógica Fuzzy. Abstract This work is intended to provide control strategies for improvements in the control system of the Vale pellet plant in São Luis, Maranhão, Brazil. The current installed plant control is a conventional Proportional Integral Derivative (PID) well suitable for regular day-by-day operations, but featuring bad performance for occasional plant re-start. In order to improve the control performance, we are proposing the use of Feedback-Error-Learning (FEL) and Multi-Network-Feedback-Error-Learning (MNFEL) strategies, since both can coupled together current PID control. In order to provide a wide comparison, other unconventional strategies, as PI-Fuzzy controller, also are included in the experiments and discussion of this work. Keywords: Adaptive control. Neural networks. Fuzzy logic.